Association between BCL2 interacting protein 3 like (BNIP3L) genetic polymorphisms and the risk of multiple myeloma in China - Qicai Wang; Yu Wang; Jing Wu; Xing Xie; Hongping Qin; Chunni Huang; Zhongqing Li; Zhian Ling; Ruolin Li (Hematology)
Background: The BCL2 interacting protein 3-like (BNIP3L) protein is involved in multiple myeloma (MM) development and progression. This study aims to explore the connection between BNIP3L single-nucleotide polymorphisms (SNPs) and MM.Methods: SNaPshot was used to examine six SNP loci of the BNIP3L gene in enrolled subjects. The relationship between these loci and MM susceptibility and prognosis was explored. Survival analysis was used to evaluate the impact of different factors on patient survival.Results: The rs2874670 AA genotype and A allele were associated with increased MM risk (P < 0.05). The CCACAC haplotype had a higher frequency in MM, while CCGCAC had a higher frequency in normal patients (all P < 0.05). Patients with R-ISS stage I and II had higher survival rates than those with stage III (P < 0.05). Patients, who received chemotherapy followed by autologous stem cell transplantation, had longer survival time than those who only received chemotherapy (P < 0.05). Low levels of LDH and β2-MG were associated with better survival rates (P < 0.05). Cox regression identified that LDH levels, β2-MG levels, and R-ISS staging were the risk factors for the death of MM. Mann-Whitney U test found a significant difference in survival time between MM patients with different BNIP3L rs2874670 genotypes after BD chemotherapy (P < 0.05).Conclusion: To our knowledge, this is the first study to find that BNIP3L rs2874670 could increase MM susceptibility in China. Different BNIP3L rs2874670 genotypes may affect the prognosis of MM patients receiving BD chemotherapy.